Manajemen Operasional: Perencanaan Rekrutmen Sumber Daya Manusia untuk Meningkatkan Mutu Pelayanan PT. Bank Rakyat Indonesia, Tbk - Herlina; Lubis, Donly Wance; Afrizal, Fajri; Winanda, Vanny Nuari; Lusiana (SAFE-Network, 2025)
This study aims to analyze human resource recruitment planning to improve the quality of banking services at PT. Bank Rakyat Indonesia, Tbk. This research uses interviews with employees at PT. Bank Rakyat Indonesia, Tbk to gather information regarding human resource planning, recruitment processes, and the factors affecting the quality of human resources within the company. The results of the study indicate that a well-structured human resource planning process is crucial for the company to meet the staffing needs of vacant positions. The recruitment process at Bank BRI involves several stages, including job analysis, selection, interviews, psychological tests, and medical exams. Additionally, the company utilizes both internal and external recruitment sources to obtain qualified labor. The main challenge in human resource management is the varying educational backgrounds of employees, which are not always focused on economics or banking, posing a challenge to increasing productivity and banking-related knowledge. As a solution, Bank BRI provides training and development programs to enhance employee competencies in banking. With a structured and effective recruitment plan, PT. Bank Rakyat Indonesia, Tbk can build a competent workforce, ultimately leading to improved service quality and customer satisfaction.